Pop Culture Study to Enhance the Awareness of Eco-Literacy - Kusumadewi, Kenya Permata (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This paper discusses the concept of enhancing eco-literacy through pop culture, which is the product of pop culture, such as music, songs, and books in fostering ecological awareness and sustainable practices. It synthesizes current research, identifies the trends and gaps, critically evaluates the impact of various pop culture elements, and suggests directions for future research to better leverage pop culture in promoting eco-literacy.